Applications and Challenges of E-Learning Technologies - Thakur, A (International Journal of Computer Sciences and Engineering, 2023)
The present work investigates the application of e-learning in the education system in the situations of social distancing caused by the pandemic COVID-19. The likelihoods and challenges in the execution of e-learning have been discussed. The recent widely used platforms for e-learning are presented in the present work. An investigation of these platforms, along with their advantages and disadvantages have been addressed. Based upon the analysis conducted, the challenges for the future enhancement and successful deployment of e-learning are addressed.